Deliberation or Aggression? Unpacking Toxic Disinhibition in TikTok's Political and Educational Discourse - Roul Alvaro Prasetyo; Elsa Nurhalisa; Budi Mulyono (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2026)
This study aims to analyze the forms of citizens' expressions and participation in the digital public sphere, as well as to uncover public opinion anomalies on a state official's policy post. The research subjects were netizens' comments on the